Crystal structure of chalcone synthase, a key enzyme for isoflavonoid biosynthesis in soybean. Issue 1 (25th August 2020) - Imaizumi, Riki; Mameda, Ryo; Takeshita, Kohei; Kubo, Hiroki; Sakai, Naoki; Nakata, Shun; Takahashi, Seiji; Kataoka, Kunishige; Yamamoto, Masaki; Nakayama, Toru; Yamashita, Satoshi; Waki, Toshiyuki
Abstract: Isoflavonoid is one of the groups of flavonoids that play pivotal roles in the survival of land plants. Chalcone synthase (CHS), the first enzyme of the isoflavonoid biosynthetic pathway, catalyzes the formation of a common isoflavonoid precursor. We have previously reported that an isozyme of soybean CHS (termed GmCHS1) is a key component of the isoflavonoid metabolon, a protein complex to enhance efficiency of isoflavonoid production. Here, we determined the crystal structure of GmCHS1 as a first step of understanding the metabolon structure, as well as to better understand the catalytic mechanism of GmCHS1.